Characterization, pretreatment and saccharification of spent seaweed biomass for bioethanol production using baker's yeast. (July 2016) - Sudhakar, M.P.; Merlyn, Ravel; Arunkumar, K.; Perumal, K.
Abstract: Seaweeds are marine macroalgae found abundantly and viewed as potential source of phycocolloids to produce biofuel. In this study, seaweed spent biomass obtained from alginate production industry and biomass obtained after pigment extraction were found to contain a considerable amount of phycocolloids. These two spent biomasses were investigated for the production of ethanol. In this study, the red seaweed spent biomass of Gracilaria corticata var corticata showed higher content of polysaccharide (190.71 ± 30.67 mg g −1 dry weight) than brown seaweed spent biomass (industrial) (136.28 ± 30.09 mg g −1 dry weight). Hydrolysis of spent biomasses with different concentrations of sulfuric acid (0.1%, 0.5% and 1%) was also investigated. Brown seaweed spent biomass and red seaweed spent biomass exhibited high amount of sugar in 0.5% and 1% sulfuric acid treatment, respectively. Proximate and ultimate composition of seaweed spent biomasses were analysed for energy value. The FT-Raman spectra exhibited similar stretches for both acid hydrolysed spent biomasses with their respective standards. Ethanol produced through a fermentation process using spent hydrolysates with baker's yeast at pH 5.3 was found to be significant. The ethanol yield from brown seaweed spent biomass and red seaweed spent biomass was observed to be 0.011 g g −1 and 0.02 ± 0.003 g g −1 respectively, when compared with YPD (0.42 ± 0.03 g g −1 ) andd -galactose (0.37 ± 0.04 g g −1 ) as standard on day 4. The present study revealed the possibility of effective utilization of spent biomass from seaweed industry for ethanol production. Highlights: Mild acid pretreatment and autoclaving found effective for hydrolysis of seaweed spent biomass. Industrial seaweed spent biomass fermented using baker's yeast found promising for ethanol production. Ethanol yield was found significant with standard substrates. Seaweed spent biomass was characterized.